Analisis faktor Keaktifan Kader dalam Kegiatan Posyandu - Shermina Oruh (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; The development and improvement of the quality of posyandu services is strongly influenced by the participation of the community, including cadres. Objectives; knowing the factor analysis of cadre activity in posyandu activities. Method; quantitative research with a descriptive analytical cross-sectional study approach, data collection is done by distributing questionnaires to respondents. The data analysis used was univariate and bivariate with the help of SPSS. Results; shows that there is a relationship between the level of education, knowledge, appreciation and distance from home with the activeness of cadres in posyandu activities. Conclusion: there is a relationship between education, knowledge, appreciation and distance from home with cadre activity in posyandu activities